DAMPAK DESENTRALISASI FISKAL TERHADAP KINERJA FISKAL DAERAH DAN KETAHANAN PANGAN DI WILAYAH PROVINSI JAWA BARAT - Wiwiek Rindayati; Bunasor Sanim; M Parulian Hutagaol; Hermanto Siregar (School of Business, Bogor Agricultural University (SB-IPB), 2007)
The implementation of fiscal decentralization in accordance with Law No 32/2004 regarding local government and No. 33/2004 regarding inter-government fiscal relationship was considered as the new era management and local goverment budgets. The objectives of this study are (1) to analyze factors affecting regional fiscal performance, regional economy performance, poverty ond food security performance, (2) to evaluate impact of fiscal decentralization policy on poverty and food security in West Java.The descriptive analysis and simultaneous econometrical models were used in this study, using pooled time series data of 1995-2005 and cross section data of 13 kabupaten estimated using the 2SLS method. The result of the study shows that the DAU was the source of 68 persen of regional income.The routine expenditures were the largest regional expenditures (77 persen). The policy of increasing wages of agricultural has affectively increased food security and poverty alleviation in West Java.